Coping with the loan transition in professional association football. (May 2022) - Kent, Sofie; Neil, Rich; Morris, Robert
Abstract: The present study generated a qualitative examination of male professional football players' experiences of stress during the loan transition using the Demand Resources and Individual Effects (DRIVE) Model. Purposeful sampling was used to recruit participants ( M age = 23; SD = 2.5) from various Premier League ( n = 2), Championship ( n = 8), and League (n = 1) clubs across the UK who have experienced a loan to another club. Guided by a critical realist philosophical orientation, semi-structured interviews were deductively developed based upon the DRIVE model to stimulate contextual discussion about the pre-transition resources (e.g. organizational support), perceived transition demands (e.g. performance pressure) and appraisals. Finally, players were asked to discuss their strategies for coping (e.g. situational coping) with loan demands and if they deemed this coping to be effective. Braun and Clarke's (2013) thematic content analysis was utilised. Deductive thematic analysis was used to identify and evidence themes that were articulated in relation to the demands experienced, appraisals associated with such demands, and the coping strategies used to manage these demands. An inductive approach was used to code sub-themes from the data, on the basis of players' specific experiences that had not yet been exemplified in the existing literature. This study presented loan transition demands ( performance and organizational ), contextual individual differences ( situational coping, dispositional coping, and protective factors ) and loan resources ( transition preconditions and during loan ) that may assist individuals' performance and well-being. Practitioners would be advised to work with players on facilitating pre-transition resources and identify perceived demands they consider important to their transition process. Future research should seek to explore the loan transition within elite female football. Highlights: This is the first study to present an examination of the stress experience of the loan transition. This study has identified the various individual differences and loan resources that may mediate and/or moderate individuals' performance and well-being. Practitioners would be advised to work with players on facilitating pre-transition resources and identify perceived demands they consider important to their transition process.